2020
DOI: 10.1055/s-0040-1716688
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Antoni: A Surgeon's Guide to the Vestibular Schwannoma Microenvironment

Abstract: Introduction Vestibular schwannomas (VS) are histologically benign tumors arising from cranial nerve VIII. Far from a homogenous proliferation of Schwann cells, mounting evidence has highlighted the complex nature of the inflammatory microenvironment in these tumors. Methods A review of the literature pertaining to inflammation, inflammatory molecular pathways, and immune-related therapeutic targets in VS was performed. Relevant studies published up to June 2020 were identified based on a literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
2
1
Order By: Relevance
“…Emerging evidence underscores the increasing importance of immune cells within the microenvironment. Contrary to the conventional notion that only mutated Schwann cells bear relevance in VS pathogenesis, our findings reveal a substantial presence of immune cells, particularly macrophages, in these benign tumors ( 22 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Emerging evidence underscores the increasing importance of immune cells within the microenvironment. Contrary to the conventional notion that only mutated Schwann cells bear relevance in VS pathogenesis, our findings reveal a substantial presence of immune cells, particularly macrophages, in these benign tumors ( 22 ).…”
Section: Discussioncontrasting
confidence: 99%
“… 12 Inflammation is present in both sporadic and NF2 -SWN VS with similar levels of tumour-associated leukocyte infiltration, 8 , 13 , 14 and inflammation—specifically increased circulating chemokines and macrophage infiltration—correlates with increased sporadic VS growth. 15–18 Along with macrophage niches, tumour-infiltrating lymphocytes such as T-cells and, to a much lesser extent, B cells are found within both sporadic and NF2 -SWN VS. 19 , 20 Both macrophages and T-cells within the tumour immune microenvironment have garnered attention for their potentials as therapeutic targets in VS, 10 , 21 , 22 but as yet, no studies have aimed to identify whether targeted immunotherapeutics would be equally efficacious in both sporadic and NF2 -SWN VS, nor whether the more common sporadic VS samples could be used to assess therapeutics to treat NF2 -SWN VS and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized that immune cells, such as macrophages and B and T lymphocytes, infiltrate the VS (Hannan et al., 2020 ). Evidence from both ex vivo and in vivo studies showed that inflammation and the immune microenvironment in VS play a key role in the pathophysiology of VS, and research on targeted molecular therapies for VS has drawn attention (Hannan et al., 2022 ; Lewis et al., 2019 ). Although VS is a benign tumor, it appears that the immune system checkpoint can be circumvented by expressing PD‐L1.…”
Section: Discussionmentioning
confidence: 99%